Facile route to gold-graphene electrodes by exfoliation of natural graphite under electrochemical conditions. (October 2016) - Poizot, Philippe; Humbert, Bernard; Ewels, Christopher P.; Mevellec, Jean-Yves; Stephant, Nicolas; Simonet, Jacques
Abstract: An original and practical procedure for preparing graphene-modified gold electrodes has been developed by careful control of the electrochemical exfoliation process of natural graphite. Pre-exfoliated (intercalated) graphite is first mechanically deposited onto a gold electrode. A cathodic treatment is then performed in N, N -dimethylformamide containing tetraalkylammonium salts at potential lower than −2 V vs. Ag/AgCl. This erodes the carbon coating through exfoliation of graphite particles. The result of this simple process, as identified by Raman spectroscopy, is a highly stable carbon surface made of graphene sheets, that gives well reproducible voltammetric responses (both in potential and intensity). Confocal Raman microspectrometry demonstrates that the bonded graphene phase consists of either 1 or 3 layers over micron-sized areas of the gold substrate. These layers can then subsequently be used as a trap to fix different organic groups. This easy and highly reproducible process could greatly simplify gold-graphene electrode production in the field of electrochemistry of graphite and its parent compounds.